Impact of Grameen Bank micro credit on change in livelihood status of women beneficiaries (Journal of the Bangladesh Agricultural University, 2010)
Grameen Bank (GB) is one of the largest NGO working with the socio-economic upliftment of the poor section, specially women of the society. The main focus on the present study is to determine change in livelihood status of women beneficiaries of GB in twenty selected centers of Jaforgonj north of Debidwar branch under Comilla district; and to identify the existing problems faced by GB participants. Data were collected from 100 randomly selected sample (15% of population), out of population size 663 of GB beneficiaries. Data indicated that change in livelihood status scores of the respondents varied from 4 to 24. The average change in livelihood status score was 13.94. The largest proportion (62 percent) of women belonged to medium, compared to 25 percent and 13 percent belong to low and high change in livelihood status categories respectively. Results of t-test on change of livelihood status in three dimensions namely ‘change of farm and house hold materials', ‘change of housing, health and sanitation' and ‘change of annual family income' in terms of ‘before' and ‘after' involvement were found highly significant. Out of 11 selected characteristics, education, annual income, credit availability, communication with GB employee and staff and attitude towards micro-credit program of GB were positively significant and only age and non-localite behaviour were negatively significant with dependent variable of change in livelihood status. Family size, farm size, organizational participation and attitude towards community did not show any significant relationship with change in livelihood status. Problems faced by beneficiaries in respect of ‘lack of sufficient amount of credit' was the most serious problems, credit disbursement delayed was the second problem and the third problem was ‘belief on dogmatism and fatalism' with problem index 199 among the six existing problems. Keywords: Grameen Bank; Micro credit; Livelihood status;  Women beneficiaries DOI: 10.3329/jbau.v7i2.4750 J. Bangladesh Agril. Univ. 7(2): 381-386, 2009